2008
DOI: 10.1159/000162283
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Herpes Simplex Virus Hepatitis in a Patient with Esophageal Cancer under Radiochemotherapy

Abstract: Background: Herpes simplex virus (HSV) infections are frequent. However, HSV hepatitis is rare and may lead to a life-threatening condition. Case Report: A 68-year-old patient with a locally advanced and inoperable esophageal carcinoma was treated with induction chemotherapy and combined chemoradiation. After a total of 9 weeks of treatment, he developed fulminant liver failure of unknown origin and died a few days later. Surprisingly, the post mortem examination revealed an HSV infection of the esophagus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Indeed 80 out of the 149 (54%) published cases occurred in immunocompromised patients, and 45 of them in solid organ transplant recipients. HSV-2 was responsible for 62% of cases [1][2][3][4][5][6][7][8]. Interestingly, the present patient had no apparent immunosuppression and, in the absence of specific IgM and IgG, we retained the diagnosis of primary infection, despite his advanced age.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Indeed 80 out of the 149 (54%) published cases occurred in immunocompromised patients, and 45 of them in solid organ transplant recipients. HSV-2 was responsible for 62% of cases [1][2][3][4][5][6][7][8]. Interestingly, the present patient had no apparent immunosuppression and, in the absence of specific IgM and IgG, we retained the diagnosis of primary infection, despite his advanced age.…”
Section: Discussionmentioning
confidence: 61%
“…Acute herpes simplex virus (HSV) hepatitis is a rare cause of acute liver failure (ALF), with only 148 reported cases [1][2][3][4][5][6][7][8]. Because of the poor prognosis it has been suggested to initiate specific antiviral therapy as soon as HSV hepatitis is suspected, while waiting for virological confirmation [9].…”
mentioning
confidence: 99%
“…Grimm et al have previously reported a fulminant case of HSV hepatitis in a patient undergoing chemoradiotherapy for oesophageal cancer. 4 Our case differs in that there was a ten-week interval between treatment and infection in a seemingly well patient. Although myelosuppression is rare during treatment with capecitabine, the blood tests following radiotherapy showed a lymphopenia, suggesting a degree of immunological compromise, but this largely recovered before surgery.…”
Section: Discussionmentioning
confidence: 62%
“…Peracute fatal herpes simplex hepatitis developed in 1 patient (unique patient number(UPN)17)4weeksafterthestartofCRT [18].Anotherpatient(UPN19)didnotstartCRTbecausethetumor volume was too large according to the radiooncologist and, therefore,retrospectivelythispatientwouldnothavemetthe trialinclusioncriteria.Radiotherapywasstoppedearly(after 39.6Gy)inathirdpatient(UPN15)becausetheradiooncologist was concerned about intolerable late sequalae resulting fromaverylargeirradiationvolume.…”
Section: Feasibility and Toxicitymentioning
confidence: 99%